Community Media 2.0: A Report from the ‘Co-Creative Communities’ Forum - Edmond Maura (Cultural Science)
Participatory digital culture presents major challenges to all traditional media outlets, but it presents very direct challenges to the community broadcast sector, which was established from the outset as local, community-driven and participatory. These and other issues were the focus of a recent forum at the Australian Centre for the Moving Image in Melbourne (Co-Creative Communities, 8–9 November 2012). The forum was part of a national research project, which has been exploring how Australian community arts and media organisations are responding to participatory digital culture, social media and user-led innovation. Focusing on the organisations that presented at the symposium, the paper examines how community-interest media is making the most of new and social media platforms. It considers examples of participatory digital media that have emerged from the community broadcast sector, but it also considers local, collaborative, community-interest media projects developed by public broadcasters and organisations involved in arts, social justice and development. Drawing on forum transcripts and follow-up research the essay describes some of the key trends shaping how community-interest media organisations and independent producers are working with participatory digital culture, and with what success.